Effect of Micronutrient Fertilization on Soil Fertility and Production of Maize - Nugroho, Gabryna Auliya; Novalia Kusumarini; Wachidiyah Romadhoni; Syahrul Kurniawan (Jurnal Online Pertanian Tropik, 2024)
Balanced fertilization in both macro and micronutrients is one strategy in soil fertility management to prevent microelement deficiencies. This fertilization type could increase plant growth and production as well as maintain soil fertility. This research aimed to examine the role of micro fertilization on supporting plant productivity and soil fertility. Research that was conducted in Dau, Malang, East Java was designed using a Randomized Block Design (RBD) with 9 treatments, ie B0 (Control), B1 (100% standard fertilization), B2 (100% standard fertilization and 50% ZnCuB), B3 (100% standard fertilizer and 100% ZnCuB), B4 (100% standard fertilizer and 150% ZnCuB), B5 (75% standard fertilizer and 50% ZnCuB), B6 (75% standard fertilizer and 100% ZnCuB), B7 (75% basic fertilizer and 150% ZnCuB), and three replications of each. 100% of basic fertilization referred to 440 kg Urea/ha, 250 kg SP-36/ha, and 350 kg KCl/ha, while 100% micro fertilizer ZnCuB (4:6:6) was 19 kg/ha. Reducing 25% of basic fertilizer combined with 150% of micro fertilizer (28.5 kg/ha ZnCuB) resulted in a significant increase in plant growth and production by 54% to control. Furthermore, micronutrient fertilizers could maintain soil fertility as well as prevent soil acidification.